Comparison of end‐of‐life care for people living in home settings versus residential aged care facilities: A nationwide study among Australian general practitioners. (6th April 2021) - Ding, Jinfeng; Johnson, Claire E.; Auret, Kirsten; Ritson, Dianne; Masarei, Carolyn; Chua, David; Licqurish, Sharon; Mitchell, Geoffrey; Cook, Angus
Abstract: We have little knowledge of differences in end‐of‐life care between home settings and residential aged care facilities (RACFs) where people spend most of their last year of life. This study aimed to compare end‐of‐life care between home settings and RACFs from the perspective of Australian general practitioners (GPs). A descriptive study was conducted with 62 GPs from Western Australia, Queensland and Victoria. Participants were asked to provide reports on end‐of‐life care of decedents in their practice using a validated clinic‐based data collection process developed by our team between September 2018 and August 2019. Of the 213 reported expected deaths, 66.2% mainly lived at home in the last year of life. People living at home were more likely to die at a younger age (median 77 vs. 88, p  < 0.001), to be male (51.1% vs. 33.3%, p  = 0.01) and to die of cancer (53.9% vs. 4.2%, p  < 0.001) compared to those in RACFs. There were no significant differences between the two patient groups for seven out of the eight assessed symptoms, except nausea. GPs' perceived roles in caring for patients and levels of their involvement in provision of common palliative care services were comparable between the two groups. The usual accommodation setting was most frequently considered the preferred place of death in both groups. However, more home residents ended up dying in hospital compared to RACF residents. There were significantly higher frequencies of end‐of‐life discussions (ORs ranged 5.46–9.82 for all topic comparisons) with GPs associated with people living at home versus RACFs. One opportunity for improved care is through promoting greater involvement of GPs in end‐of‐life discussions with RACF residents and staff. In general, more Australians could potentially remain at home until death if provided with greater access to essential specialist palliative care services and supportive services in home settings.